Simbiosis Mutualistis (PAI Dan Pendidikan Nasional) - Yuhana, Nihayatul Laili (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2015)
Abstract: Education is a conscious attempt adults to guide and direct the personality and ability of the students in formal or informal education. Islamic religious education is "the efforts in a systematic and pragmatic in helping the students, so that they live according to the teachings of Islam. Objectives included in the curriculum of Islamic education is to form students to be a man of faith and fear of god almighty one and noble or be man of faith and piety in accordance religion. Policy of religious education in Indonesia can be found in legislation that essentially confirms the guarantee of the right to personal freedom, namely the right to freedom religion. The rules also become the meter to assess the degree of accuracy and truth in the religious education policy formulation. Islamic educational institutions (Madrasah Diniyah) serves to educate anan-child drop-outs, children who do not have the opportunity to enter formal educational institutions and at the same time add to and strengthen the implementation of Islamic education in schools due to the limited hours of Islamic education lessons at school.